Uji Aktivitas Antioksidan Ekstrak Etanol Umbi Keladi Tikus (Typhonium Flagelliforme (L.) Blume) - Elvira Santi; Andi Juaella Yustisi; Nurfitria Junita (Journal Syifa Sciences and Clinical Research, 2023)
Rodent tuber (Typhonium flagelliforme (L.) Blume) is a medicinal plant used by the community as a drug. This plant is nutritious because one of chemical contents is triterpenoid which is having a role as the free radical scavenger that can lead to degenerative diseases. The aim of the research is to determine the extract antioxidant activities of rodent tuber (Typhonium flagelliforme (L.) Blume) based on the binding of free radicals of 1,1-diphenyl-2-picrylhydrazyl. Extract of rodent tuber (Typhonium flagelliforme (L.) Blume) was obtained by maceration method, the sample was macerated by using ethanol of 96%. This research used DPPH method. The antioxidant activity against free radical were measured by mean of UV-Vis spectrophotometry at a wavelength of 516 nm and calculated the value of IC50. The results showed that each rodent tuber extract (Typhonium flagelliforme (L.) Blume) has IC50 for the ethanol extract was 74.359 Âµ/mL and the comparison of quercetin with the value IC50 was 10.298 Âµg/mL respectively